Birth outcomes following antiretroviral exposure during pregnancy: Initial results from a pregnancy exposure registry in South Africa - Ushma C. Mehta; Cari van Schalkwyk; Prineetha Naidoo; Arthi Ramkissoon; Otty Mhlongo; Niren R. Maharaj; Niree Naidoo; Karen Fieggen; Michael F. Urban; Shaun Krog; Alex Welte; Mukesh Dheda; et al. (AOSIS, 2019)
Background: In 2013, a pregnancy exposure registry and birth defects surveillance (PER/BDS) system was initiated in eThekwini District, KwaZulu-Natal (KZN), to assess the impact of antiretroviral treatment (ART) on birth outcomes. Objectives: At the end of the first year, we assessed the risk of major congenital malformations (CM) and other adverse birth outcomes (ABOs) detected at birth, in children born to women exposed to ART during pregnancy. Method: Data were collected from women who delivered at Prince Mshiyeni Memorial Hospital, Durban, from 07 October 2013 to 06 October 2014, using medicine exposure histories and birth outcomes from maternal interviews, clinical records and neonatal surface examination. Singleton births exposed to only one ART regimen were included in bivariable analysis for CM risk and multivariate risk analysis for ABO risk. Results: Data were collected from 10 417 women with 10 517 birth outcomes (4013 [38.5%] HIV-infected). Congenital malformations rates in births exposed to Efavirenz during the first trimester (T1) (RR 0.87 [95% CI 0.12-6.4; p = 0.895]) were similar to births not exposed to ART during T1. However, T1 exposure to Nevirapine was associated with the increased risk of CM (RR 9.28 [95% CI 2.3-37.9; p = 0.002]) when compared to the same group. Other ABOs were more frequent in the combination of HIV/ART-exposed births compared to HIV-unexposed births (29.9% vs. 26.0%, adjusted RR 1.23 [1.14-1.31; p 0.001]). Conclusion: No association between T1 use of EFV-based ART regimens and CM was observed. Associations between T1 NVP-based ART regimen and CM need further investigation. HIV- and ART-exposed infants had more ABOs compared to HIV-unexposed infants.